Overview Facility Service Passengers at the Ferry Port Cape Fires Regency Banyuasin South Sumatra Province in 2022 - Febriansyah; Chairul Insani Ilham; Yosion Yudiarto Lumbantungkup (IWTJ : International Water Transport Journal, 2022)
Ferry Port Tanjung Api-Api serves the Tanjung Api-Api – Tanjung Kalian ( Muntok ) route , as the main port that connects between Province need existence appropriate service _ with base law in order to implementation activity good port . However fact still there is a number of indicator service to passengers who don't in accordance with provisions . Based on from condition that , author To do studies literature to problems found in the Port.U for analyze passenger service problems by calculating the level of conformity of passenger service standards according to existing conditions based on related survey _ with service to passengers at the port . After that results than method _ this will be analyzed with level suitability in accordance with Regulation Director General Communication Land No. KP 5062 of 2020 About Guidelines Evaluation Standard Services at the Ferry Port . After being analyzed by the researcher, it was concluded that the percentage level suitability Standard Service Passengers at the Ferry Port Cape Fires by 23.67% and the discrepancy by 25.65% from 49.32% percentage maximum set _ for standard service passenger based on Legal Basis , then from that researchers also make proposal solving problem for Fulfill level suitability standard service Passengers at the Ferry Port Cape Fires in the District Banyuasin South Sumatra Province.